1997
DOI: 10.1002/(sici)1097-0215(19971021)74:5<502::aid-ijc4>3.3.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Combined analysis of p53 and vascular endothelial growth factor expression in colorectal carcinoma for determination of tumor vascularity and liver metastasis

Abstract: Recent studies have demonstrated that the p53 tumor suppressor gene plays an important role in controlling tumor angiogenesis. We examined the expression of p53 and vascular endothelial growth factor (VEGF), a well-characterized angiogenic inducer, together with microvessel density to investigate the role of p53 in the regulation of angiogenesis and its clinical significance in human colorectal carcinoma. Surgically resected specimens of 163 colorectal carcinomas were studied by immunohistochemical staining fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 5 publications
(7 reference statements)
5
29
1
Order By: Relevance
“…The newborn vessels have important eVects on the aggressive phenotype and the metastatic potential of tumors (Yu et al 2003). In agreement with our results, previous studies have shown that VEGF expression is an independent prognostic factor in predicting patients' prognosis (Kang et al 1997;Lee et al 2000), while others have reported no such association (Takahashi et al 1997). Moreover, no signiWcant correlation of VEGF expression with pathological parameters of prognostic value, such as disease stage, was detected in our cases.…”
Section: Discussionsupporting
confidence: 89%
“…The newborn vessels have important eVects on the aggressive phenotype and the metastatic potential of tumors (Yu et al 2003). In agreement with our results, previous studies have shown that VEGF expression is an independent prognostic factor in predicting patients' prognosis (Kang et al 1997;Lee et al 2000), while others have reported no such association (Takahashi et al 1997). Moreover, no signiWcant correlation of VEGF expression with pathological parameters of prognostic value, such as disease stage, was detected in our cases.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, in line with previous observations on colorectal carcinomas of different TNM stages [24,27,[29][30][31], high MVD and VEGF expression appear to be related to higher MVD microvessel density, DID dead of independent disease, DOD dead of disease progression risk in stage I colorectal carcinoma. Although tumor neo-angiogenesis alone is not sufficient for the development of metastases, the formation of new blood vessels may increase the opportunity for malignant cells to enter the blood stream and thus to give rise to metastases [32].…”
Section: Discussionsupporting
confidence: 91%
“…No immunoreaction was present in the vessels within the normal distant mucosa, thus confirming that CD105 is a more specific marker for neo-angiogenesis than the commonly used pan-endothelial markers. Statistical analysis revealed the existence of a significant correlation between VEGF expression and MVD, in line to what was previously reported by other authors [27][28][29][30]; indeed, cases characterized by higher VEGF amount displayed significantly higher MVD counts. The presence of such a M male, F female, ID intensity distribution Previous studies have demonstrated that high VEGF as well as high MVD behave as significant negative prognostic factors for colorectal cancer-specific survival [27,[29][30][31].…”
Section: Discussionsupporting
confidence: 90%
“…It is also reported that there is no relationship between the two expressions in lung (Fontanini et al 1998;Giatromanolaki et al 1998), gastric , and colon ) cancers as well as endometrial cancer (Fujiwaki et al 1999). There are contradictory studies on the correlation of MVC and p53 expression in showing a positive relationship (Fontanini et al 1997(Fontanini et al , 1998(Fontanini et al , 1999Kang et al 1997;Takahashi et al 1998) and a negative relationship (Fujiwaki et al 1999;Giatromanolaki et al 1998;Salvesen et al , 1998. In endometrial cancer, similar contradictory results are also reported on the relation of MVC and tumor histological grade (Abla®a et al 1995;Fujiwaki et al 1999;Kaku et al 1997;Obermeir et al 1999;).…”
Section: Discussionmentioning
confidence: 92%